Analysis of Good Governance Implementation on Village Financial Management - Sari, Djuwita; Rabin Ibnu, Zainal; Haqiqi, Teuku Muhammad (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
The principle of good governance also controls the village government to carry out good governance and avoid fraud during the village financial management process. This type of research is a quantitative descriptive study using primary data and data collection techniques using questionnaires. This study uses the analysis of the validity test, reliability test, simple linear regression test, coefficient of determination, and hypothesis test. The study concluded that implementing good governance positively and significantly affected village financial management. In this study, it is hoped that the village government will be able to provide the community with correct information about village financial management and easy access for people who need information.